Teacher Wellbeing as a Cornerstone of Student Success in Foreign Language Education - Leandro Delgado-Fernández; José Luis Sardiñas-Companioni; Adis Eliany Puerto-Valdés (Educación y Sociedad)
This article delves deep into the crucial link between teacher wellbeing and student success.Through a qualitative exploratory and descriptive paradigm, the research includes a theoreticalreview, a survey, and a focus group to explore the current state of the multifaceted relationshipbetween teacher wellbeing and the quality of learning and student outcomes in the ForeignLanguage Major at the University of Ciego de Ávila. The findings reveal that teacher wellbeingis decisive in ensuring student success, as happy and fulfilled teachers are more likely toprovide positive, engaging, and effective learning experiences to their students. However, it isoften hindered by numerous challenges, including burnout, excessive workload, lack of support,and inadequate compensation. These challenges can negatively impact teacher morale, job satisfaction, and performance, leading to decreased student engagement, achievement, and overall success. In response, a range of innovative and practical solutions to support teacher wellbeing are proposed, leading to happier teachers and more successful students.